Effects of Eye Movement with PNF Neck Movement on Trunk Stability and Standing Position Balance Ability of Chronic Stroke Patients - Kim, Dong Hoon; Kim, Kyung-Hun; Lee, Suk-Min (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2019)
Objective We investigated the effects of eye movement with PNF neck movement on trunk stability and standing position balance ability of chronic stroke patients.Methods A total of 30 patients were randomly divided into EMPN group and CON group. EMPN group was performed 60 min three times a week for 8 weeks in eye movement and PNF neck movement. CON group performed conservative treatment for 60min. The trunk stability was measured by the Trunk impairment scale (TIS) and the standing balance ability test was performed by Center of Pressure (COP), Limited of Stability (LOS), Berg Balance Scale (BBS) and Functional Reach Test (FRT).Results There was a significant difference (P<0.05) between before and after training in both groups, and EMPN group showed significant improvement in both groups.Conclusions In this study, we confirmed oculogyration and neck movement by PNF have positive effects on the trunk stability and the standing position balance ability of chronic stroke patients.
Keywords: hemiplegie; physiotherapie; rehabilitation; stroke